Preparation method and application of Si / C composite negative electrode material based on CVD rotary kiln gradient deposition coating
By employing a stepwise deposition coating technique using gradient-varying silane and carbon source gases in a CVD rotary kiln, the problem of uneven dispersion of silicon-carbon anode materials was solved, improving the electrochemical performance and stability of the materials and achieving more efficient lithium-ion battery performance.
Patent Information
- Application Number
- CN202511122879.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-12
- Publication Date
- 2025-11-18
AI Technical Summary
In the preparation of silicon-carbon anode materials using existing CVD technology, silanes and carbon are unevenly dispersed inside and on the surface of porous carbon, resulting in unstable electrochemical performance of the material and affecting the cycle life and first discharge efficiency of lithium-ion batteries.
A gradient-structured Si/C composite anode material is formed by stepwise deposition and coating of silane and carbon source gases in a CVD rotary kiln. Uniform dispersion of silane deposition and carbon coating is achieved by controlling the gas flow rate, temperature and rotation speed.
The electrochemical performance of the Si/C composite anode material was improved, enhancing cycle stability and first discharge efficiency, while reducing the specific surface area to minimize side reactions.
Smart Images

Figure CN120964819A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to the field of silicon-carbon negative electrode materials, in particular to a Si / C composite negative electrode material preparation method based on CVD rotary kiln gradient deposition coating and application. BACKGROUND
[0002] As the core energy storage device of new energy vehicles and 3C digital electronic products, lithium ion batteries have an urgent need for energy density improvement. Silicon (Si) negative electrode has become a promising next-generation negative electrode material due to its ultra-high theoretical specific capacity (~4200 mAh / g). However, the severe volume expansion (>300%) of silicon during charging and discharging leads to particle pulverization, active material failure, rapid capacity decay, and poor cycle life, which seriously hinders its commercial application.
[0003] After extensive reporting and research by the academic and industrial communities, chemical vapor deposition (CVD) is considered the most effective method for preparing a new generation of gas-phase silicon-carbon negative electrode materials. That is, silane is deposited and cracked inside the porous carbon material, and then coated with carbon to enhance the electrical conductivity and particle stability of the material. At the same time, it also reduces the specific surface area and reduces the occurrence of side reactions of the silicon-carbon negative electrode material. However, the existing CVD technology uses a rotary kiln device, and the particles are not uniformly dispersed during tumbling, resulting in uneven deposition and carbon coating of silane (SiH4) inside and on the surface of the porous carbon, which causes significant differences between the silicon-carbon negative electrode material particles, ultimately affecting the electrochemical performance of the silicon-carbon negative electrode material.
[0004] Therefore, it is urgent to develop a new technology that uses carbon source concentration gradients to achieve pore depth closure and surface active site passivation, ensuring uniform dispersion of silane deposition and coated carbon materials in silicon-carbon negative electrodes, effectively reducing the specific surface area, reducing the occurrence of side reactions, and improving the first discharge efficiency and cycle stability of silicon-carbon negative electrode materials. SUMMARY
[0005] The purpose of the present application is to overcome one or more of the deficiencies of the prior art and provide a.
[0006] The purpose of the present application is achieved by the following technical solutions:
[0007] A Si / C composite negative electrode material preparation method based on CVD rotary kiln gradient deposition coating, mainly comprising the following steps:
[0008] The raw material porous carbon is continuously or batchwise loaded into the CVD rotary kiln, and the gas in the kiln is replaced under inert gas protection and then heated to a set temperature;
[0009] Step-by-step deposition and coating of gradient-changing silane (SiH4) and carbon source gas are performed;
[0010] Dynamic CVD deposition is carried out at a set temperature field and rotating speed to form a gradient structure of silane (SiH4) deposition and carbon coating layer;
[0011] Cooling, collecting the product to obtain a CVD rotary kiln gradient deposition coated Si / C composite negative electrode material; the porous carbon is resin-based or biomass-based porous carbon.
[0012] Further, the physicochemical property index of the carbon-based skeleton material satisfies: specific surface area 1600.0~2200.0m² / g, pore volume size 0.8~1.2cm³ / g, pore size 1.3~2.0nm, micropore ratio >85.0%.
[0013] Further, the particle size of the porous carbon skeleton material satisfies: D0≥1.0μm; D10≥3.5μm, D507.0~9.0μm, D100≤25.0μm.
[0014] Further, the CVD deposition gas is silane gas (SiH4), which requires a purity of >99.999%; the carbon coating gas is acetylene (C2H2), which requires a purity of >99.99%; the inert protective gas is one or more of helium (He), neon (Ne), argon (Ar), krypton (Kr), xenon (Xe) and nitrogen (N2) mixed gas.
[0015] Further, the preparation stage of the gradient deposition coating process comprises the following steps:
[0016] S1: furnace tube static state, inert protective gas is introduced for 1.0~15.0min, flow rate 0.0~20.0L / min, test the air tightness of the rotary kiln equipment to ensure no leakage;
[0017] S2: inert protective gas is introduced at a flow rate of 0.0~30.0L / min for 0.0~60.0min under the static state of the furnace tube, to exclude the oxygen content in the CVD rotary kiln to <10.0ppm.
[0018] Further, the silane cracking stage of the gradient deposition coating process comprises the following steps:
[0019] After the internal temperature of the CVD rotary kiln equipment is raised to 400.0~600.0℃, silane (SiH4) gas and inert protective gas are slowly introduced, and the mass fraction of silicon deposited in the porous carbon is designed to be 40.0~60.0wt%;
[0020] The first gradient deposition silane (SiH4) stage, the silane (SiH4) gas flow rate is 0.0~15.0L / min, the deposition time is 0.0~720.0min, and inert protective gas is synchronously introduced, the gas flow rate is 0.0~20.0L / min, and the equipment rotation speed is adjusted to 0.0~10.0 / rpm;
[0021] The second gradient deposition silane (SiH4) stage, the silane (SiH4) gas flow rate is 0.0~15.0L / min, the deposition time is 0.0~720.0min, and inert protective gas is synchronously introduced, the gas flow rate is 0.0~20.0L / min, and the equipment rotation speed is adjusted to 0.0~10.0 / rpm;
[0022] The third gradient deposition silane (SiH4) stage, the silane (SiH4) gas flow rate is 0.0~15.0L / min, the deposition time is 0.0~720.0min, and inert protective gas is synchronously introduced, the gas flow rate is 0.0~20.0L / min, and the equipment rotation speed is adjusted to 0.0~10.0 / rpm.
[0023] Further, in the gradient deposition coating process, after the silane (SiH4) deposition stage is completed, a coating gas coating stage is entered, which specifically includes the following steps:
[0024] The coating gas cracking temperature range is 550.0~650.0℃, and the designed carbon coating mass fraction is 0.0~10.0wt%; the first gradient coating gas coating stage, the coating gas flow rate is 0.0~20.0L / min, the coating time is 0.0~600.0min, and inert protective gas is synchronously introduced, the gas flow rate is 0.0~20.0L / min, and the equipment rotation speed is adjusted to 0.0~10.0 / rpm;
[0025] The second gradient coating gas coating stage, the coating gas flow rate is 0.0~20.0L / min, the coating time is 0.0~600.0min, and inert protective gas is synchronously introduced, the gas flow rate is 0.0~20.0L / min, and the equipment rotation speed is adjusted to 0.0~10.0 / rpm;
[0026] The third gradient coating gas coating stage, the coating gas flow rate is 0.0~20.0L / min, the coating time is 0.0~720.0min, and inert protective gas is synchronously introduced, the gas flow rate is 0.0~20.0L / min, and the equipment rotation speed is adjusted to 0.0~10.0 / rpm; after the silane (SiH4) gas deposition and acetylene (C2H2) gas coating are completed, cooling to room temperature to obtain a CVD rotary kiln gradient deposition coated Si / C composite negative electrode material.
[0027] Provided is an application of a Si / C composite negative electrode material for a lithium ion battery negative electrode.
[0028] The present application has the following advantages:
[0029] (1) By using the CVD rotary kiln gradient deposition coating technology, the silane deposition and carbon coating on the porous carbon material are uniformly dispersed, and the material uniformity is improved;
[0030] (2) By using the gradient change of the gas parameters and the dynamic deposition process, the interface stability of the silicon-carbon negative electrode material is improved, and the specific surface area is reduced to reduce the side reaction;
[0031] (3) By using the step-by-step deposition coating to form a gradient structure, the electrochemical performance of the silicon-carbon negative electrode material is improved, and the cycle stability and the first discharge efficiency are enhanced. BRIEF DESCRIPTION OF DRAWINGS
[0032] Figure 1 The Si / C scanning electron microscope image of the CVD rotary kiln gradient deposition coating of the biomass porous carbon of the present application embodiment 1;
[0033] Figure 2 The Si / C EDSMapping image of the CVD rotary kiln gradient deposition coating of the biomass porous carbon of the present application embodiment 1. DETAILED DESCRIPTION
[0034] The technical solutions of the present application will be described below in conjunction with the embodiments, and obviously, the described embodiments are only a part of the embodiments of the present application, but not all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor are within the scope of protection of the present application.
[0035] A Si / C composite negative electrode material preparation method based on CVD rotary kiln gradient deposition coating is provided, which mainly includes the following steps:
[0036] The raw material porous carbon is continuously or batchwise loaded into the CVD rotary kiln, and after replacing the gas in the kiln under inert gas protection, the temperature is raised to the set temperature;
[0037] The gradient change of the silane and carbon source gas is introduced for step-by-step deposition coating;
[0038] Dynamic CVD deposition is carried out at the set temperature field and rotational speed to form a silane deposition and carbon coating layer with a gradient structure;
[0039] Cooling, collecting the product to obtain the CVD rotary kiln gradient deposition coated Si / C composite negative electrode material; the porous carbon is resin-based or biomass-based porous carbon.
[0040] The physicochemical property indexes of the carbon-based skeleton material satisfy: specific surface area 1600.0-2200.0 m² / g, pore volume size 0.8-1.2 cm³ / g, pore size 1.3-2.0 nm, and micropore ratio > 85.0%.
[0041] The particle size of the porous carbon skeleton material satisfies: D0≥1.0 μm; D10≥3.5 μm, D50 7.0-9.0 μm, and D100≤25.0 μm.
[0042] The CVD deposition gas is silane gas, which requires a purity of > 99.999%; the carbon-coating gas is acetylene, which requires a purity of > 99.99%; and the inert protective gas is one or more mixed gases selected from helium, neon, argon, krypton, xenon and nitrogen.
[0043] The preparatory stage of the gradient deposition coating process comprises the following steps:
[0044] S1: furnace pipe static state, inert protective gas is introduced for 1.0-15.0 min at a flow rate of 0.0-20.0 L / min, the air tightness of the rotary kiln equipment is tested to ensure no leakage;
[0045] S2: inert protective gas is introduced at a flow rate of 0.0-30.0 L / min for 0.0-60.0 min under the static state of the furnace pipe, and the oxygen content in the CVD rotary kiln is excluded to < 10.0 ppm.
[0046] The silane cracking stage of the gradient deposition coating process comprises the following steps:
[0047] After the internal temperature of the CVD rotary kiln equipment is raised to 400.0-600.0 °C, silane gas and inert protective gas are slowly introduced, and the mass fraction of silicon deposited in the porous carbon is designed to be 40.0-60.0 wt%;
[0048] In the first gradient deposition silane stage, the silane gas flow rate is 0.0-15.0 L / min, the deposition time is 0.0-720.0 min, and inert protective gas is introduced synchronously at a gas flow rate of 0.0-20.0 L / min, and the equipment speed is adjusted to 0.0-10.0 rpm;
[0049] In the second gradient deposition silane stage, the silane gas flow rate is 0.0-15.0 L / min, the deposition time is 0.0-720.0 min, and inert protective gas is introduced synchronously at a gas flow rate of 0.0-20.0 L / min, and the equipment speed is adjusted to 0.0-10.0 rpm;
[0050] The third gradient deposition silane stage has a silane gas flow rate of 0.0-15.0 L / min, a deposition time of 0.0-720.0 min, and an inert protective gas is synchronously introduced at a gas flow rate of 0.0-20.0 L / min, and the equipment rotation speed is adjusted to 0.0-10.0 / rpm.
[0051] In the gradient deposition coating process, after the silane deposition stage ends, a coating gas coating stage is entered, which specifically includes the following steps:
[0052] The coating gas cracking temperature interval is 550.0-650.0℃, and the designed carbon coating mass fraction is 0.0-10.0wt%;The first gradient coating gas coating stage has a coating gas flow rate of 0.0-20.0 L / min, a coating time of 0.0-600.0 min, and an inert protective gas is synchronously introduced at a gas flow rate of 0.0-20.0 L / min, and the equipment rotation speed is adjusted to 0.0-10.0 / rpm;
[0053] The second gradient coating gas coating stage has a coating gas flow rate of 0.0-20.0 L / min, a coating time of 0.0-600.0 min, and an inert protective gas is synchronously introduced at a gas flow rate of 0.0-20.0 L / min, and the equipment rotation speed is adjusted to 0.0-10.0 / rpm;
[0054] The third gradient coating gas coating stage has a coating gas flow rate of 0.0-20.0 L / min, a coating time of 0.0-720.0 min, and an inert protective gas is synchronously introduced at a gas flow rate of 0.0-20.0 L / min, and the equipment rotation speed is adjusted to 0.0-10.0 / rpm;After the silane gas deposition and the acetylene gas coating end, cooling to room temperature, a CVD rotary kiln gradient deposition coated Si / C composite negative electrode material is obtained.
[0055] Example 1
[0056] This embodiment is a preparation method and application of a Si / C composite negative electrode material based on a CVD rotary kiln gradient deposition coating, which specifically includes the following steps:
[0057] Step 1: Select biomass-based porous carbon, which has a specific surface area of 1750.0 m2 / g, a pore volume size of 0.85 cm3 / g, a pore size of ~1.7 nm, and a micropore ratio of ~85.0%. The particle size is: D01.17 μm, D103.92 μm, D507.03 μm, and D10018.56 μm.
[0058] Step 2: CVD rotary kiln airtightness verification, furnace tube static state, nitrogen gas flow rate 2.0 L / min, time 30.0 min, test the airtightness of the rotary kiln equipment. Ensure no leakage. Continue to pass nitrogen, flow rate 1.0 L / min, time 30.0 min, exclude the oxygen content in the rotary kiln furnace to <10.0 ppm.
[0059] Step 3: Start the temperature rising program, wait for the temperature in the rotary kiln furnace to rise to 480.0℃, slowly pass in silane gas, design the mass fraction of porous carbon deposited silicon in silane (SiH4) to be 55.0wt%, and the actual cracking efficiency of silane (SiH4) is calculated according to 99.99%.
[0060] Step 4: First gradient deposition silane (SiH4) stage, silane (SiH4) gas flow rate 1.0 L / min, deposition time 360.0 min, and simultaneously pass in inert protective gas nitrogen, gas flow rate 1.5 L / min, adjust the equipment speed 3.0 / rpm.
[0061] Second gradient deposition silane stage, silane (SiH4) flow rate 0.5 L / min, deposition time 480.0 min, and simultaneously pass in inert protective gas nitrogen, gas flow rate 1.0 L / min, equipment speed maintained at 5.0 / rpm.
[0062] Third gradient deposition silane stage, silane (SiH4) flow rate 1.0 L / min, deposition time 180.0 min, and simultaneously pass in inert protective gas nitrogen, gas flow rate 1.0 L / min, adjust the equipment speed 3.0 / rpm.
[0063] Step 5: After the silane deposition stage is completed, turn off the acetylene gas, continue to pass in inert protective gas nitrogen 1.0 L / min, CVD rotary kiln equipment is heated to 590.0℃, enter the coating gas coating stage, design the carbon coating content ~2.0wt%.
[0064] First gradient coating gas coating stage, acetylene gas flow rate 1 L / min, deposition time 60.0 min, and simultaneously pass in inert protective gas nitrogen, gas flow rate 1.0 L / min, equipment speed maintained at 3.0 / rpm.
[0065] Second gradient coating gas coating stage, acetylene gas flow rate 0.5 L / min, deposition time 360.0 min, and simultaneously pass in inert protective gas, gas flow rate 1.0 L / min, adjust the equipment speed 5.0 / rpm.
[0066] The third gradient coating gas coating stage, acetylene gas flow rate 1 L / min, deposition time 120.0 min, and synchronously pass in inert protective gas nitrogen, flow rate 1.0 L / min, adjust the equipment rotation speed 3.0 / rpm. After the coating gas is finished, stop the acetylene gas, keep the inert protective gas nitrogen flow rate 2.0 L / min, after cooling to room temperature, pass through the sieve, remove the magnet and other processes, the CVD rotary kiln gradient deposition coated biomass-based Si / C composite negative electrode material can be obtained. As shown in Figure 1 The scanning electron microscope image of the biomass-based Si / C composite negative electrode material prepared in Example 1 is shown in FIG. 1. The silicon deposition layer and the carbon coating layer are clearly observed to be continuously and uniformly distributed in the material surface and internal pore structure, without obvious agglomeration phenomenon, which reflects the ordered microstructure formed by the gradient deposition coating process.
[0067] Referring to Figure 2 The EDS Mapping image of the biomass-based Si / C composite negative electrode material prepared in Example 1 is shown in FIG. 2, which directly shows the distribution of silicon and carbon elements in the material. Both of them show gradient change characteristics along the depth of the material pores, which further verifies the uniform and gradient distribution effect of silicon and carbon achieved by the gradient deposition coating process.
[0068] Electrochemical performance test: The slurry preparation ratio is that the silicon-carbon negative electrode material: carbon nanotube: conductive carbon black SP: PAA binder is calculated according to the mass fraction, and the ratio is 80.0wt%:5wt%:5wt%:10wt% respectively. The electrode design load is 4.0 mg / cm2, and the electrode design compactness is 1.0 g / cm3. The separator is selected as Celgard2400 microporous separator, and the electrolyte ratio is 1 mol / L LiPF6(EC / DEC, i.e. the volume ratio of ethylene carbonate / diethyl carbonate is 1:1). The counter electrode uses metal lithium, and is assembled into a CR2032 button cell in a vacuum glove box. The electrochemical performance test is carried out in Wuhan Lan electric test system, the charge-discharge voltage test interval is 0.005~1.5V, and the charge-discharge rate is 0.1C.
[0069] The same biomass porous carbon as in Example 1 is selected as the skeleton material. The CVD rotary kiln gas tightness test and inert gas replacement are carried out as in Example 1. In the silane deposition stage, the rotary kiln temperature is raised to 480.0°C: the silane gas (SiH4) flow rate is 2.0 L / min, the inert protective gas flow rate is 1.0 L / min, the rotary kiln speed is 3.0 / rpm, and the total amount of silane gas (SiH4) introduced is the same as the total amount of carbon-coated gas acetylene in Example 1. In the coating gas coating stage: the CVD rotary kiln temperature is raised to 590.0°C: the acetylene gas flow rate is 2.0 L / min, the nitrogen gas flow rate is 1.0 L / min, the total amount of acetylene gas introduced is the same as in Example 1, and the rotary kiln speed is 3.0 / rpm. After the coating stage is completed, the acetylene gas is turned off and nitrogen is continuously introduced until it cools to room temperature. By sieving and removing the magnet, a CVD rotary kiln deposited silane and carbon-coated biomass-based silicon-carbon negative electrode material can be obtained.
[0070] Example 2
[0071] This embodiment is a preparation method and application of Si / C composite negative electrode material based on CVD rotary kiln gradient deposition coating. The specific steps include: designing a silicon deposition mass percentage of 55.0wt%, a carbon coating content of 2.0wt%, and selecting a resin-based porous carbon with the following physical and chemical indicators: specific surface area ~2000.0 m2 / g, pore volume 0.91 cm3 / g, pore size ~1.9 nm, and micropore ratio ~90.0%. The particle size is: D01.32 μm, D104.11 μm, D507.47 μm, and D10019.32 μm. The remaining steps are carried out as in Example 1 to obtain a CVD rotary kiln gradient deposition coated resin-based Si / C composite negative electrode material.
[0072] In Control Example 2,
[0073] The same resin-based porous carbon as in Example 2 is selected as the skeleton material, and the silicon deposition ratio and carbon coating ratio are the same as in Example 2. The remaining steps are carried out as in Control Example 1 to obtain a CVD rotary kiln deposited silane and carbon-coated resin-based silicon-carbon negative electrode material.
[0074] Example 3
[0075] This embodiment is a preparation method and application of Si / C composite negative electrode material based on CVD rotary kiln gradient deposition coating. Biomass porous carbon is selected as the raw material, and the physical and chemical indicators are the same as in Example 1. The key point is to adjust the silicon deposition mass percentage to 50.0wt% and the carbon coating ratio to 2.0wt% to obtain a CVD rotary kiln gradient deposition coated biomass-based Si / C composite negative electrode material.
[0076] Control Example 3
[0077] The same biomass porous carbon as in Example 3 is selected as the skeleton material, the silicon deposition ratio and the carbon coating ratio are the same as in Example 3. The remaining test steps are performed according to the control example 1, and the biomass-based silicon-carbon negative electrode material deposited with silane and coated with carbon in a CVD rotary kiln can be obtained.
[0078] Example 4
[0079] This embodiment is a preparation method and application of Si / C composite negative electrode material based on CVD rotary kiln gradient deposition and coating. Resin-based porous carbon is selected as the raw material, and the physicochemical indexes are the same as in Example 1. The key point is to adjust the silicon deposition mass percentage to 50.0wt%, and the carbon coating ratio to 2.0wt%, so that the resin-based Si / C composite negative electrode material deposited and coated by CVD rotary kiln gradient deposition can be obtained.
[0080] In the control example 4, the silane deposition amount is designed to be 50.0%, the carbon coating ratio is 2.0wt%, and the same resin-based porous carbon as in Example 4 is selected as the skeleton material. The remaining test steps are performed according to the control example 1, and the resin-based silicon-carbon negative electrode material deposited with silane and coated with carbon in a CVD rotary kiln can be obtained.
[0081] Table 1: Test data results of Si / C negative electrode materials prepared in different examples
[0082] Test item Designed amount of silane deposition (wt%) Actual silicon content (wt%) Specific surface area (m2 / g) First reversible specific capacity (mAh / g) First discharge efficiency (%) 100 cycle retention rate (calculated from the second cycle) (%) Example 1 55.0% 53.23 2.09 1937.49 93.01 89.72 Example 2 55.0% 56.34 1.48 1962.84 92.38 89.43 Example 3 50.0% 48.94 2.16 1821.31 93.81 91.23 Example 4 50.0% 49.37 1.45 1774.38 93.92 92.91 Comparative Example 1 55.0% 52.34 3.21 1909.13 91.89 84.23 Comparative Example 2 55.0% 54.42 4.67 1912.15 90.30 85.02 Comparative Example 3 50.0% 46.83 5.44 1792.42 91.22 86.63 Comparative Example 4 50.0% 47.91 3.53 1759.47 90.75 85.54
[0083] Through the CVD rotary kiln gradient deposition and coating technology, uniform dispersion of silane deposition and carbon coating on the porous carbon material is realized, and the material uniformity is improved. Through the gradient change of gas parameters and dynamic deposition process, the interface stability of the silicon-carbon negative electrode material is improved, and the specific surface area is reduced to reduce the side reaction. Through the step-by-step deposition and coating to form a gradient structure, the electrochemical performance of the silicon-carbon negative electrode material is improved, and the cycle stability and the first discharge efficiency are enhanced.
[0084] The above description is only the preferred embodiments of the present application, and it should be understood that the present application is not limited to the forms disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the concepts described herein by the above teachings or related art or knowledge. Any modification and change made by those skilled in the art without departing from the spirit and scope of the present application shall be within the protection scope of the appended claims of the present application.
Claims
1. A method for preparing Si / C composite anode materials based on CVD rotary kiln gradient deposition coating, characterized in that, It mainly includes the following steps: Porous carbon raw materials are continuously or batch-loaded into a CVD rotary kiln, and the kiln gas is replaced under inert gas protection before being heated to the set temperature. A gradient of silane and carbon source gases is introduced for stepwise deposition and coating. Dynamic CVD deposition is performed under a set temperature field and rotation speed to form a silane deposition and carbon coating layer with a gradient structure. The product is cooled and collected to obtain a Si / C composite anode material coated by gradient deposition in a CVD rotary kiln; the porous carbon is resin-based or biomass-based porous carbon.
2. The preparation method according to claim 1, characterized in that, The physicochemical properties of the carbon-based framework material meet the following requirements: specific surface area 1600.0~2200.0 m² / g, pore volume 0.8~1.2 cm³ / g, pore size 1.3~2.0 nm, and micropore ratio >85.0%.
3. The preparation method according to claim 1, characterized in that, The particle size of the porous carbon framework material satisfies the following conditions: D0≥1.0μm; D10≥3.5μm; D507.0~9.0μm; D100≤25.0μm.
4. The preparation method according to claim 1, characterized in that, The CVD deposition gas is silane gas with a purity requirement of >99.999%; the carbon coating gas is acetylene gas with a purity requirement of >99.99%; and the inert protective gas is one or more mixed gases selected from helium, neon, argon, krypton, xenon, and nitrogen.
5. The preparation method according to claim 1, characterized in that, The preparatory stage of the gradient deposition coating process includes the following steps: S1: With the furnace tube in a static state, introduce inert protective gas for 1.0~15.0 min at a flow rate of 0.0~20.0 L / min to test the airtightness of the rotary kiln equipment and ensure there is no leakage; S2: With the furnace tube in a static state, inert protective gas is introduced at a flow rate of 0.0~30.0L / min for a time of 0.0~60.0min to remove the oxygen content in the CVD rotary kiln to <10.0ppm.
6. The preparation method according to claim 1, characterized in that, The silane pyrolysis stage of the gradient deposition coating process includes the following steps: Once the internal temperature of the CVD rotary kiln reaches between 400.0 and 600.0℃, silane gas and inert protective gas are slowly introduced. The designed silicon deposition mass fraction within the porous carbon is 40.0 to 60.0 wt%. In the first gradient deposition stage of silane, the silane gas flow rate is 0.0~15.0 L / min, the deposition time is 0.0~720.0 min, and an inert protective gas is introduced simultaneously at a flow rate of 0.0~20.0 L / min, while the equipment rotation speed is adjusted to 0.0~10.0 rpm. In the second gradient deposition stage of silane, the silane gas flow rate is 0.0~15.0 L / min, the deposition time is 0.0~720.0 min, and an inert protective gas is introduced simultaneously at a flow rate of 0.0~20.0 L / min, while the equipment rotation speed is adjusted to 0.0~10.0 rpm. In the third gradient silane deposition stage, the silane gas flow rate is 0.0~15.0 L / min, the deposition time is 0.0~720.0 min, and an inert protective gas is introduced simultaneously with a gas flow rate of 0.0~20.0 L / min, and the equipment rotation speed is adjusted to 0.0~10.0 rpm.
7. The preparation method according to claim 1, characterized in that, In the gradient deposition coating process, after the silane deposition stage is completed, the coating gas coating stage begins, which specifically includes the following steps: The pyrolysis temperature range of the coated gas is 550.0~650.0℃, and the designed carbon coating mass fraction is 0.0~10.0wt%. In the first gradient coating gas coating stage, the coating gas flow rate is 0.0~20.0L / min, the coating time is 0.0~600.0min, and an inert protective gas is introduced simultaneously at a flow rate of 0.0~20.0L / min, and the equipment rotation speed is adjusted to 0.0~10.0 / rpm. In the second gradient gas coating stage, the coating gas flow rate is 0.0~20.0 L / min, the coating time is 0.0~600.0 min, and an inert protective gas is introduced simultaneously with a gas flow rate of 0.0~20.0 L / min, and the equipment rotation speed is adjusted to 0.0~10.0 rpm. In the third gradient gas coating stage, the coating gas flow rate is 0.0~20.0 L / min, the coating time is 0.0~720.0 min, and an inert protective gas is introduced simultaneously at a flow rate of 0.0~20.0 L / min, while the equipment rotation speed is adjusted to 0.0~10.0 rpm. After the silane gas deposition and acetylene gas coating are completed, the material is cooled to room temperature to obtain the Si / C composite anode material coated by gradient deposition in a CVD rotary kiln.
8. The application of the Si / C composite anode material prepared by any one of claims 1-7, characterized in that, The Si / C composite anode material is used as the anode for lithium-ion batteries.
Citation Information
Cited By
Silicon-carbon negative electrode material with multi-layer structure and preparation method and reaction device of silicon-carbon negative electrode material
CN121416408A
Silicon-carbon negative electrode material and fluidization preparation method thereof
CN121484037A